2017
DOI: 10.1128/aac.02177-16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Pharmacokinetic Drug-Drug Interaction of Antimalarial Drugs α/β-Arteether and Sulfadoxine-Pyrimethamine

Abstract: Antimalarial drug combination therapy is now being widely used for the treatment of uncomplicated malaria. The objective of the present study was to investigate the effects of coadministration of intramuscular α/β-arteether (α/β-AE) and oral sulfadoxine-pyrimethamine (SP) on the pharmacokinetic properties of each drug as a drug-drug interaction study to support the development of a fixed-dose combination therapy. A single-dose, open-label, crossover clinical trial was conducted in healthy adult Indian male vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As first-line antimalarial medicines, arteether is safe, low-toxic and well tolerable. Furthermore, outcomes from a limited number of clinical trials provide encouraging evidence for their excellent antitumor activities [ 54 , 55 ]. However, some problems such as poor solubility, toxicity and controversial mechanisms of action hamper their use as effective antitumor agents in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As first-line antimalarial medicines, arteether is safe, low-toxic and well tolerable. Furthermore, outcomes from a limited number of clinical trials provide encouraging evidence for their excellent antitumor activities [ 54 , 55 ]. However, some problems such as poor solubility, toxicity and controversial mechanisms of action hamper their use as effective antitumor agents in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…However, some problems such as poor solubility, toxicity and controversial mechanisms of action hamper their use as effective antitumor agents in the clinic. In order to accelerate the use of arteether in the clinic, researchers have recently developed novel therapeutic approaches including developing novel derivatives, manufacturing novel nano-formulations and combining arteether with other drugs for cancer therapy [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, both treatments were found not to interfere significantly with each other's pharmacokinetics in the reported group of healthy volunteers, supporting the use of these two treatments as a new combination therapy for malaria. (29) Naphthoquine (Fig. 4) is a 4-aminoquinoline developed in China and synthesised in 1986.…”
Section: Malaria Chemotherapymentioning
confidence: 99%
“…Its combination with clindamycin has already been trialed and has presented initial success for malaria treatment, however, a more recent trial reported unfavorable results for this combination. (9,29) Fosmidomycin was also trialed in combination with primaquine in Gabon and showed promising results. The study was designed as a proof-of-concept and evaluated the efficacy, tolerability and safety of the combination therapy and thus did not include a control population.…”
Section: Malaria Chemotherapymentioning
confidence: 99%
“…The half-life of Sulfadoxine and Pyrimethamine is~169 hours and~111 hours α/β-Arteether is a CYP3A4/5 substrate, whereas sulfadoxine-pyrimethamine has no interaction with CYP3A4/5 22 .…”
Section: Fig 2 Doxycycline 21mentioning
confidence: 99%